Leukocyte Counts and Ratios Are Predictive of Stroke Outcome and Hemorrhagic Complications Independently of Infections - Semerano, Aurora; Strambo, Davide; Martino, Gianvito; Comi, Giancarlo; Filippi, Massimo; Roveri, Luisa; Bacigaluppi, Marco (Frontiers in Neurology, 2020)
BACKGROUND – Ischemic stroke patients show alterations in peripheral leukocyte counts that may result from the sterile inflammation response as well as the occurrence of early infections. We here aimed to determine whether alterations of circulating leukocytes in acute ischemic stroke are associated with long-term functional outcome and hemorrhagic complications, independently of the occurrence of infections. METHODS – Blood laboratory values of patients with acute ischemic stroke presenting within 4.5 hours from symptom onset were collected. Leukocyte subsets were analysed in relation to three-month functional outcome, mortality, and parenchymal hemorrhagic transformation (PH). A multivariable logistic regression analysis, considering the occurrence of early post-stroke infections, was performed for each outcome measure. RESULTS – Five-hundred-ten patients were included in the study. Independently of infections, good functional outcome was associated with a lower neutrophil to lymphocyte ratio (NL-R, OR 0.906 [95%CI 0.822-0.998]), a higher lymphocyte count (OR 1.547 [95%CI 1.051-2.277]), a higher eosinophil count (OR 1.027 [95%CI 1.007-1.048]) and a higher eosinophil to leukocyte ratio (EoLeu-R, OR 1.240 [95%CI 1.071-1.436]) at admission. Death within three months was associated with higher NL-R (OR 1.103 [95%CI 1.032-1.179]) as well as with lower eosinophil counts (OR 0.909 [95%CI 0.827-0.999]). Patients developing parenchymal hemorrhagic transformation had higher neutrophil counts (OR 1.420 [95%CI 1.197-1.684]) as well as a higher NL-R (OR 1.192 [95%IC 1.088-1.305). CONCLUSION – Leukocyte subtype profiles in the acute phase of ischemic stroke represent a predictor of outcome independently of infections. Stroke-evoked sterile inflammation is a pathophysiological relevant mechanism that deserves further investigation.